2008
DOI: 10.1111/j.1526-4610.2007.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and Lipid Levels While Taking Topiramate for Migraine

Abstract: Our results suggest a need for monitoring serum UA levels in patients receiving TPM. We should perhaps prescribe a low-UA diet and advice to drink much more water in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…TPM reduces enzymes responsible for fatty acids synthesis and enhances those of fatty acid β-oxidation [57], as well as mitochondrial function [58], which accelerates the β-oxidation rate of fatty acids. Albeit scarce data are available regarding the effect of TPM on TC level, yet previous studies support our finding, where TC level was decreased in epileptic adults treated with TPM [59], and migraine patients receiving TPM [60] and alcoholic patients subjected to TPM [61]. However, the exact mechanism for this effect has not been clearly elucidated.…”
Section: Discussionsupporting
confidence: 61%
“…TPM reduces enzymes responsible for fatty acids synthesis and enhances those of fatty acid β-oxidation [57], as well as mitochondrial function [58], which accelerates the β-oxidation rate of fatty acids. Albeit scarce data are available regarding the effect of TPM on TC level, yet previous studies support our finding, where TC level was decreased in epileptic adults treated with TPM [59], and migraine patients receiving TPM [60] and alcoholic patients subjected to TPM [61]. However, the exact mechanism for this effect has not been clearly elucidated.…”
Section: Discussionsupporting
confidence: 61%
“…This indication is off-label and requires further study; particularly because a high BMI at baseline is not predictive of which migraine patients will lose weight on topiramate (Alberici et al, 2009). Topiramate monotherapy in migraine has been associated with significant elevations of serum uric acid, increasing risk of nephrolithiasis, and non-significant serum triglyceride elevation (Koçer et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Lipid levels in TPM-treated neurological patients have been examined in few previous investigations, only one of which was in adults with epilepsy; that study included only female patients (Franzoni et al, 2007;Kocer et al, 2008;Genc et al, 2010). These studies found no change in TC after TPM treatment; one found a small decline in HDL-C only (Genc et al, 2010).…”
Section: Discussionmentioning
confidence: 99%